Review of current methods of preparation and distribution of DMEK graft at the eye banks - Shalini Singh; Priyanka Pantola; Sunita Chaurasia; Sujata Das; Somasheila Murthy (Indian Journal of Ophthalmology)
The scope of eye banking activities has been expanding with the advances and techniques of keratoplasty. With the popularity of descemet membrane endothelial keratoplasty (DMEK) in the recent decade, there is a need to adopt the preparation of DMEK tissues in the eye banks. This necessitated surgical training of the eye bank technicians, development of infrastructure in the eye bank, innovative methods of graft preparation, and delivery for the surgery at distant surgery centers. Eye banks across various countries have devised and adopted different methods of providing DMEK grafts based on the demands and preferences of corneal surgeons. This review focuses on the strategies of DMEK graft preparation and its distribution at the eye banks.